The Influence of Service Quality on Customer Satisfaction at The Ritz-Carlton Bali Hotel - I Ketut Andika Putra Laksana; Ida Ayu Kalpikawati; Ni Luh Ketut Sri Sulistyawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study is intended to be able to evaluate the influence of service quality on customer satisfaction. A total of 100 respondents were presented as samples using purposive sampling techniques. The data used are quantitative data on service quality and customer satisfaction. The results of the analysis show the presence of a positive influence and its significance between (x) and (y), with t count greater than t table (13.272> 1.984) and its significance level is smaller than α (0.001 <0.05). Therefore, it can be concluded that service has a positive impact and its significance is apparent on customer satisfaction at The Ritz-Carlton, Bali.